Identifying and Working with Elementary Asperger’s Students in Rural America - Allen, Barton; Loiacono, Vito; Vacca, James S. (Journal of the American Academy of Special Education Professionals, 2010)
Currently, somewhere in a rural American school sits an elementary-aged student who has been labeled by a teacher and his/her peers as the "Little Professor" according to the Asperger’s Syndrome Coalition of the United States. The onset of Asperger’s Syndrome is recognized and occurs later than what is typical of autism. A significant number of children are diagnosed after age three, with most diagnosed between the age of five and nine. Children with Asperger’s Syndrome generally do not have cognitive or language delay. Social deficits begin at the start of school and they fall just below the typical range. For students with Asperger’s Syndrome the result of these deficits is that they never fit in with their classmates. Thus Asperger’s Syndrome students slip through the cracks because they tend to be bright and quirky and these traits tend to isolate them from their classmates. Asperger’s Syndrome is a life-long disorder and if it is identified at an early age and appropriate interventions are put in place at home and school, an AS child will have the opportunity to grow and mature and have a productive life as an adult. We as educators should consider the presence of Asperger’s Syndrome students in our classrooms as a true gift and not as a burden. These children have gifts, skills, and feelings that need to be nurtured and strengthened in our rural schools.